Platform WEB Based District Health Information System Versi 2 (DHIS2) dalam Pembuatan Disease Registry - pradea wulandari (Minat Sistem Informasi Manajemen Kesehatan Fakultas Kedokteran UGM, 2022)
Background: The development of information systems in Indonesia is now increasingly sophisticated and fast. One of the health information systems used in Indonesia and used as a data warehouse is DHIS2 (District Health Information System Version 2). The purpose of the DHIS2 version was to utilize modern technology with an independent web-based platform and database that facilitates efficient and effective management of national data and as a DHIS2 data warehouse it can be used to create an online-based disease registry form. At the hospital Dr. Sardjito, the disease registry form has not used an electronic form. So this study aims to collaborate between the Dr. Sardjito central general hospital and FKKMK UGM to create a disease registry form, which consists of a COVID-19 form in children, epilepsy form and cancer form, web-based using DHIS2.Methods: This type of research is action research (AR). This research was conducted at Dr. Sardjito Hospital, Jalan. Health No. 1 Sekip Sinduadi, Sleman Regency, Yogyakarta Special Region in 2021. This study uses secondary data obtained from Dr.Sardjito Hospital. Secondary data analysis is done by collecting data sources, creating files to import data into DHIS2 and creating visualizations and dashboards on DHIS2.Results: Compile data elements, option sets and indicators for the disease registry in the DHIS2 application. Create a registry form for cancer, COVID-19 in children and epilepsy in the DHIS2 application. Perform dual language metadata translation, namely English to Indonesian for the disease registry package. Display disease registry visualizations and dashboards and create disease registry packages to register epilepsy, covid-19 in children and cancer and the disease registry package has been published.Conclusions: Provide a form on DHIS2 for disease registration, provide a disease registration package in two languages, display visualizations and dashboards available on the DHIS2 application